A notational match analysis of the 2001 women's water polo world championships - Enomoto, I.; Suga, M.; Takahashi, M.; Komori, Y.; Minami, T.; Fujimoto, H.; Saito, M.; Suzuki, T.; Takahashi, J. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION The notational match analysis has been very popular not only in soccer and basketball but also in water polo. It will show the quality of a team or player by converting performance into statistics. The purpose of this study was to contribute to the construction of knowledge about elite women`s water polo matches by using notational match analysis. METHODS The 48 games of the FINA 2001 Women`s Water Polo World Championships, in which 12 teams participated, were analyzed with a computerized match analysis system. The quantitative measures of performance collected were as follows: attacks, shots, results of shots, personal fouls, mistakes with the ball, mistakes without the ball, and attacking time. These variables were calculated for each team for offense and defense. The qualitative variables (percentage of appearance) were derived from these collected data for each team. RESULTS The higher-ranked teams (1st to 8th) and the lower-ranked teams (9th to 12th) were compared for qualitative variables. For situations in offense, percentage of shots taken (54.1 ± 4.7 % vs 45.2 ± 4.6 % for higher teams vs lower teams) and percentage of mistakes with the ball (17.3 ± 1.4 % vs 24.7 ± 4.6 %) showed significant differences. For situations in defense, percentage of personal fouls (16.8 ± 1.3 % vs 13.6 ± 2.0 %) and percentage of goalkeeper saves (54.7 ± 7.0 % vs 40.8 ± 10.4 %) differed significantly (p<0.05). DISCUSSION These results show that: 1. On offense, the higher-ranked teams shot more frequently and made fewer mistakes than the lower-ranked teams. 2. On defense, the higher-ranked teams had more personal fouls and more goalkeeper saves than the lower-ranked teams. Thus, aspiring women`s water polo teams must bring the ball to shot situations without missing the ball, they should not hesitate to commit personal fouls, and they must have an exceptional goalkeeper.